Operations Research Techniques for Cost Minimization in Transportation - AKANNI, Saheed Busayo; Garba, M.K.; Abogunrin, O.O.; Noah, R.O. (Sigma&Mu: Journal of Mathematics Education, Mathematics, Statistics and Data Science, 2026)
Optimizing the distribution of goods from multiple suppliers to multiple customers is a key challenge in supply chain management. This study compares the suitability of three classical methods for solving a 10-supplier by 15-customer transportation problem. The data used for the study were extracted from the 2023 record of a fertilizer-producing company in Nigeria, which has 10 outlets and 15 major distributors. The results revealed that the North-West Corner Method, although simple to apply despite the fact that it is cost-inefficient. Though the Minimum Cost Method behaved better in terms of efficiency, resulting to its focus on selecting low-cost routes. However, Vogel’s Approximation Method improved the allocations by adding cost-penalty factors. This led to the lowest overall cost of the three methods. Findings from the study showed that Vogel’s Approximation Method is a practical and effective way to get close-to-best solutions in the transportation problem. Within the framework of the paper, operational guidelines regarding logistics management and cost management were provided. This provision indicates that the choice of method is significant in repetitive decision-making in supply chain systems. This study provided guidelines for logistics and cost management, because it stressed that choosing the right method is essential for making repeated decisions in supply chain systems. Hence, the study concluded that if minimizing the cost of transportation is desired Vogel’s Approximation Method is recommended for supply chain system.